Analisis Investasi dan Trading Saham Perspektif Ekonomi Islam - Ahmad Very Fadli; Karina Widya Andari (Comprehensive Journal of Islamic Studies, 2024)
Investment and trading are financial methods for gaining profits from economic activities. Stock investment tends to be long-term and focuses on passive income, with investors seeking to earn profits through dividends provided by companies for the shares they own. On the other hand, stock trading tends to be short-term capital investment, focusing on stock price fluctuations in the stock market to generate profits. The public's interest in stock trading is due to the potential to earn substantial profits in a short period. However, many people still misunderstand the difference between investing and trading stocks, leading to confusion about the distinction between the two and the boundaries that must be understood by a Muslim who wants to become an investor. This research uses the library research method, where the research activities are based on library data in processing the research material. The result of this research is that stock investment and trading are two different activities. This is evident from the way transactions are conducted. However, in Islam, both are permissible as long as they adhere to Shariah principles. The permissibility of Shariah-compliant stock investment is supported by the DSN-MUI Fatwa No. 80/DSN-MUI/III/2011.Keywords: The basis of mandatory obedience, UUP, KHI, Marriage Law, Islamic Law.